Geometry of nanoindentation cube-corner cracks observed by FIB tomography: Implication for fracture resistance estimation. Issue 10 (September 2015) - Cuadrado, N.; Seuba, J.; Casellas, D.; Anglada, M.; Jiménez-Piqué, E.
Abstract When indenting a brittle material with a sharp indenter, cracks can be generated at the corners of the imprint. From the length of these cracks, the fracture resistance can be estimated. This technique is simple and allows characterizing small volumes of materials, especially if nanoindentation cube-corners tips are used. For evaluation of fracture resistance, a number of different models based on crack morphology have been proposed. However, the morphology of the cracks is difficult to determine due to the small scales involved. In this work, indentation fracture with a cube-corner nanoindentation tip on different materials is investigated by FIB tomography to obtain the generated crack morphology. Experimental observations are rationalized in terms of applied load, tip geometry and crystal anisotropy. Once the crack morphology is visualized, the two most commonly used equations for calculating the fracture resistance are discussed. Finally, guidelines for better estimation of fracture resistance are proposed.